The Horizons of Being : The Metaphysics of Ibn al-ʿArabī in the Muqaddimat al-Qayṣarī - Ali, Mukhtar H. (Middle East and Islamic Studies E-Books Online, Collection 2020, ISBN: 9789004405868., 2020)
The Horizons of Being explores the teachings of Ibn al-ʿArabī by examining Dāwūd al-Qayṣarī's (d. 1350) Prolegomena ( muqaddima ) to his commentary, Maṭlaʿ khuṣūṣ al-kilam fī maʿānī Fuṣūṣ al-ḥikam (A Preamble of Select Discourse on the Meanings of the Fuṣūṣ al-ḥikam), referred to simply as Muqaddimat al-Qayṣarī. While his commentary represents the third in a direct line going back to Ibn al-ʿArabī through Kāshānī, Jandī and Qūnawī, it remains one of the most popular due to its thorough and accessible treatment of the Fuṣūṣ that frequently synthesizes the ideas of his predecessors. The Muqaddima stands on its own as an independent work and has been the subject of careful study. If the al-Futūḥāt al-makkiyya contains the entirety of Ibn al-ʿArabī's metaphysics which is distilled in the Fuṣūṣ, then Qayṣarī's Muqaddima can be read not just as a precis of the Fuṣūṣ but a summary of Ibn al-ʿArabī's doctrine.